Family groups of Diopsoidea and Nerioidea (Diptera: Schizophora)—Definition, history and relationships - Lonsdale, Owen (Zootaxa, 2020)
The Acalyptratae are a diverse, heterogenous assemblage of dozens of families of “higher flies” in the Schizophora (Diptera). There are ten acalyptrate superfamilies, two of which are reviewed and redefined here at the family-group level: Diopsoidea and Nerioidea. The superfamily Diopsoidea includes seven families: Diopsidae (two subfamilies and two tribes), Gobryidae, Megamerinidae, Nothybidae, Psilidae (three subfamilies), Somatiidae and Syringogastridae. The superfamily Nerioidea also includes seven families: Cypselosomatidae, Fergusoninidae, Micropezidae (five subfamilies), Neriidae, Pseudopomyzidae, Tanypezidae and Strongylophthalmyiidae. All 14 families are redescribed, figured and keyed, including notes on subordinate family-level groups. Homologies for external and genitalic characters are established, and the superfamilies and their family-level groups are discussed. A morphological phylogenetic analysis is provided, including representatives from all family-level groups in both ingroup superfamilies, as well as twelve outgroup taxa from five other acalyptrate superfamilies. Both superfamilies were supported as monophyletic, although both the Diopsoidea and its basal branches were supported by highly homoplasious characters and are here only tentatively accepted; a relationship between Diopsidae, Syringogastridae and Megamerinidae is strongly supported. Nerioidea is a well-defined group divided into three lineages, including one containing Pseudopomyzidae, Cypselosomatidae and Fergusoninidae, the latter of which was previously considered to be related to the family Agromyzidae (Opomyzoidea). Diopsoidea and Nerioidea were not found to be related.